Analysis Of The Impact Of Credit Risk And Operational Risk On Financial Stability Case Study On State-Owned Enterprises In The Banking Sub-Sector - Simamora, Helprida; Yopi (Riset Sinergi Indonesia, 2025)
Banks are business entities that collect funds from the public in the form of deposits and channel them to the public in the form of credit and/or other forms of improving the standard of living of the people. This study aims to determine the effect of credit risk and operational risk on Financial Stability. Financial Stability ratios measured using Financial Stability assets and credit risk and operational risk are measured by non-performing loans (NPL) and BOPO. Data obtained from published financial statements published by Bank Indonesia with a period of time from 2015 to 2024. The sampling technique used in this study was purposive sampling. The number of samples is 3 banking companies listed on the Indonesia Stock Exchange. The analytical method that will be used in this study is multiple linear regression to obtain a comprehensive picture of the relationship between one variable and another. Based on hypothesis testing using statistical t test and f test the results of the research show that Non Performing Loans (NPL) have a significant effect on Financial Stability, while BOPO does not have a significant effect on Financial Stability and simultaneously there is a significant influence of Non Performing Loans (NPL) and BOPO on Financial Stability